2016
DOI: 10.4314/ahs.v16i1.34
|View full text |Cite
|
Sign up to set email alerts
|

Ocular injuries and eye care seeking patterns following injuries among cocoa farmers in Ghana

Abstract: Background: The work environment of cocoa farmers exposes them to several ocular hazards that predispose them to eye diseases and injuries. However, the extent of ocular injuries and health seeking patterns following these injuries are unknown among cocoa farmers in Ghana. Objectives: To determine the prevalence of ocular injuries and health seeking behaviour following injury among cocoa farmers in Ghana. Methods: Five hundred and fifty six participants were recruited through simple random sampling using a mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 21 publications
1
10
1
Order By: Relevance
“…The 12 studies reported mean CASP grades within the range of 6.50 to 10.0 with a mean score of 7.87 (SD = 1.17). The studies covered the geographic regions of Oceania, Europe, North America, Asia, Africa, and North America (eg, one from Australia, 7 England, 18 Finland, 6 Ghana, 19 India, 8 and eight from the United States 5,11,14,20‐24 ). Six of the studies used secondary data analysis of administrative databases, 6,7,11,18,20,23 two employed a cross‐sectional design, 14,19 two used a prospective design, 8,21 one used a case‐controlled design 24 and one was a retrospective view 5 …”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 12 studies reported mean CASP grades within the range of 6.50 to 10.0 with a mean score of 7.87 (SD = 1.17). The studies covered the geographic regions of Oceania, Europe, North America, Asia, Africa, and North America (eg, one from Australia, 7 England, 18 Finland, 6 Ghana, 19 India, 8 and eight from the United States 5,11,14,20‐24 ). Six of the studies used secondary data analysis of administrative databases, 6,7,11,18,20,23 two employed a cross‐sectional design, 14,19 two used a prospective design, 8,21 one used a case‐controlled design 24 and one was a retrospective view 5 …”
Section: Resultsmentioning
confidence: 99%
“…The systematic review identified the following antecedent factors of occupational ocular injury: (a) the use of eye protection at the time of the ocular injury, 6,7,11,18‐20,23 (b) being male, 5‐7,11,14,18‐20,23 (c) exposure to biological or chemical occupational hazards, 7,14,19 (d) mechanical forces, 5,6,8,21 (e) risk‐taking behavior 11,18,19 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural eye injuries have been studied with various crops such as citrus,[ 8 ] olive[ 9 ] and cocca. [ 10 ] Nevertheless, date palm tree eye injuries have not been studied in detail except for few case reports. [ 11 12 13 14 ] We aim to study the clinical presentation, management and clinical outcome of hospitalized date palm tree eye injuries.…”
Section: Introductionmentioning
confidence: 99%
“…31 Shehab reports on biochemical response to weight loss in patients with non-alcoholic steatohepatitis. 32 Now to surgery: abdominal wall herniae in females, 33 ocular injuries and eye care among cocoa farmers in Ghana; 34 and acute burns of the hands, 35 give us a taste of surgery in Africa. So do: stapedotomy and its effect on hearing.…”
mentioning
confidence: 99%